Phylogeography of Arenaria balearica L. (Caryophyllaceae): evolutionary history of a disjunct endemic from the Western Mediterranean continental islands - Bobo-Pinilla,Javier; Barrios de León,Sara B.; Seguí Colomar,Jaume; Fenu,Giuseppe; Bacchetta,Gianluigi; Peñas de Giles,Julio; Martínez-Ortega,María Montserrat (PeerJ, 2016)
Although it has been traditionally accepted that Arenaria balearica (Caryophyllaceae) could be a relict Tertiary plant species, this has never been experimentally tested. Nor have the palaeohistorical reasons underlying the highly fragmented distribution of the species in the Western Mediterranean region been investigated. We have analysed AFLP data (213) and plastid DNA sequences (226) from a total of 250 plants from 29 populations sampled throughout the entire distribution range of the species in Majorca, Corsica, Sardinia, and the Tuscan Archipelago. The AFLP data analyses indicate very low geographic structure and population differentiation. Based on plastid DNA data, six alternative phylogeographic hypotheses were tested using Approximate Bayesian Computation (ABC). These analyses revealed ancient area fragmentation as the most probable scenario, which is in accordance with the star-like topology of the parsimony network that suggests a pattern of long term survival and subsequent in situ differentiation. Overall low levels of genetic diversity and plastid DNA variation were found, reflecting evolutionary stasis of a species preserved in locally long-term stable habitats.
Keywords: AFLP; Arenaria; Island evolution; Phylogeography; Mediterranean; Stasis; Hercynian; Plastid DNA